ANTIMICROBIAL RESISTANCE IN GRAM NEGATIVE BACILLI ISOLATED FROM BLOOD CULTURE - Kovacheva-Trpkovska, Danica; Kostovski, Marko; Jovcevski, Radomir; Labacevska-Gjatovska, Liljana; Mihajlov, Kiril; Grdanoska, Tatjana; Trpkovski, Igor; Petrovska-Basovska, Branka; Mehmeti, Blerta (Journal of Morphological Sciences, 2023)
Healthcare-associated and community-acquired infections caused by Gram-negative bacteria are serious health concerns due to the rise of antibiotic resistance. Antimicrobial resistance (AMR) is a highly concerning issue in the field of medicine today, as it has significant impacts on morbidity, mortality, and socio-economic factors. Blood samples from inpatients admitted at the Clinical Microbiology Laboratory during the study period from January 2022 until December 2023 were included in study analysis. Blood culture bottles for aerobic and anaerobic cultivation were incubated in automated BACT/ALERTÂ® 3D. For further analysis, isolated pure colonies were then identified to a bacterial species level using automated VITEKÂ® 2 COMPACT system. The most commonly isolated microorganism was Escherichia coli  22%. High proportion of E. coli isolates were resistant to ciprofloxacin (69%), ceftriaxone (60%), and trimethoprim sulfamethoxazole (58%). Acinetobacter baumannii was second most frequently isolated microorganism (11%) and showed highly resistance to almost all tested antibiotics. All isolates were resistant to amikacin, fluoroquinolones and carbapenems. Highest sensitivity was found to tobramycin (35%). Pseudomonas aeruginosa showed highest resistance to gentamicin (71%), ciprofloxacin (71%), levofloxacin (75%), imipenem (76.5%) and meropenem (69%). Klebsiella pneumoniae was detected in 11% of bacterial isolates and showed highest resistance to third-generation cephalosporins (>70%), followed by ciprofloxacin (67%) and trimethoprim sulfamethoxazole (67%). Our findings contribute valuable insights into local epidemiology and resistance trends, aiding clinicians in making informed treatment decisions. Continued surveillance and research in this area are essential for addressing the challenges posed by antimicrobial resistance and improving patient outcomes. Keywords: blood culture,   antimicrobial resistance, gram negative bacilli.